Global Weak Solutions for the Weakly Dissipative μ-Hunter–Saxton Equation - Liu, Jianjun (Ukrains’kyi Matematychnyi Zhurnal, 2013)
The paper deals with the global existence of weak solutions for a weakly dissipative μ-Hunter–Saxton equation. The problem is analyzed by using smooth data approximating the initial data and Helly’s theorem.